Photocatalyzed Synthesis of 3‐Substituted Phthalides: A Key Access to (±)‐Herbaric Acid. Issue 4 (4th January 2023) - Fortier, Lucas; Gosset, Cyrille; Lefebvre, Corentin; Pellegrini, Sylvain; Pélinski, Lydie; Bousquet, Till
Abstract: An efficient organophotocatalyzed protocol was developed for the preparation of 3‐substituted phthalides. The presented transformation was performed under particularly mild conditions within 6 h and was ultimately applied to a precursor of the herbaric acid. Abstract : Herein, we investigated a new organophotocatalyzed protocol enabling the preparation of 3‐substituted phthalides. From this work, the 1, 2, 3, 5‐Tetrakis(carbazol‐9‐yl)‐4, 6‐dicyanobenzene (4CzIPN) turned out to be a particularly efficient organophotocatalyst to promote lactone formation under visible‐light irradiation within 6 h. Ultimately, it was found that this protocol could enable the formation of racemic herbaric acid.